Linking ectomycorrhizal mushroom species richness and composition with dominant trees in a tropical seasonal rainforest - Ediriweera, A.N.; Karunarathna, Samantha C; Xu J.C.; Bandara, S.M.G.S.; Gamage, A.; Schaefer, D.A. (Mushroom Research Foundation, 2020)
Vegetation, elevation gradient and soil temperature are considered as major drivers of ECM fungi species richness. ECM sporocarps were collected during rainy seasons for two years to study the link between the distribution of ECM mushrooms with Castonopsis echinocarpa, Parashorea chinensis, and Pittosporopsis kerrii with varying elevations and soil temperatures, in a tropical rain forest Xishuangbanna, Yunnan, China. For each tree species, 60 trees of approximately the same size were selected, where half of them were growing at higher elevation levels and the rest at lower levels. The highest total counts of ECM fungi, as well as the highest species richness were produced by P. chinensis followed by C. echinocarpa and P. kerrii. Highest species richness was shown in September by P. chinensis, while P. kerrii trees had the lowest count of mushrooms across rainy seasons. Species of Boletales were recorded with highest species richness followed by species of order Agaricales around both C.echinocarpa and P.chinensis. ECM fungi count declined with increased elevation. Furthermore, fungi species richness increased positively with increased soil temperature in a tropical seasonal rainforest.